Kosakata Musik sebagai Ranah Sumber Ungkapan Metaforis - Kusumaningtyas, Adityarini; Darmojuwono, Setiawati (UI Scholars Hub, 2019)
In Indonesian, music vocabulary is not only used to describe music but also used to express various non-musical concepts. That means music vocabulary has the potential to occupy the source domain in metaphorical mapping. The study aims at describing the vocabulary of music as the source domain of metaphorical expressions in Indonesian and explaining the relation of metaphorical meanings to the music field. The study was qualitative research. The data of the study was collected from the corpus of Indonesian in the Sketch Engine. The data was Indonesian sentences having the vocabulary of nada, melodi, harmoni, and dinamika in which the contexts of sentences were used to talk about anything in non-music field. The results of the study show that the vocabulary of music in Indonesian causes the metaphor of “LIFE IS MUSIC”. The use of music vocabulary as a source domain is mainly related to the characteristics of musical vocabulary concepts that underlie the formation of metaphorical expressions in Indonesian.